Efektivitas Pendekatan Pendidikan Matematika Realistik terhadap Kemampuan Pemecahan Masalah Cerita Perkalian Pecahan Berdasarkan Variasi Gaya Belajar Siswa - Wahyu Widianti; Yoppy Wahyu Purnomo; Fery Muhamad Firdaus (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to evaluate the effectiveness of the Realistic Mathematics Education (RME) approach compared to traditional learning methods in improving elementary school students' ability to solve math problems, by considering differences in learning styles (visual, auditory, and kinesthetic). This study used a pseudo-experimental method with a posttest-only control group design. The subjects consisted of two groups of grade VI students who each received different treatments, namely learning with the RME approach and conventional learning. Data were analyzed using two-way ANOVA to identify the effect of each variable, namely the type of learning approach, type of learning style, as well as the interaction between them on mathematics learning outcomes. The results of the analysis showed that the RME approach was significantly superior in improving students' math solving ability compared to the conventional approach. In addition, a significant effect of learning styles was found, where students with visual and kinesthetic learning styles showed higher achievement than students with auditory learning styles. The interaction between learning approach and learning style was also found to be significant on students' math problem solving ability. These findings underscore the importance of applying contextual learning approaches that are aligned with students' learning characteristics to improve the quality of mathematics learning at the primary school level.